The Effectiveness of Common Cold Massage in Healing Coughs and Colds in Baby and Toddlers in Rahma Medika Clinic - Wahyu Riyanti; Bunga Romadhona Haque (Global Health Science Group, 2023)
Health problems most often experienced by a baby toddler are cough and cold due to respiratory tract irritation problems, allergies, and decreased immunity. Non-pharmacological handling of cold cough is safer to use because it does not use side effects such as drugs. One non-pharmacological way is common cold massage. The purpose of this study was to analyze the effectiveness of common cold massage on the healing time of cold cough in baby and toddlers at Rahma Medika clinic. This study was an experimental quasy design, where the researcher only intervened in one group and the other group would act as a control without randomization. This research was conducted for 1 month, April – May 2023 at the Rahma Medika clinic. The samples used in this study were 32 in the intervention group and 32 in the control group. Univariate analysis results mean cure time of the intervention group was 2.6 days and the control group was 3.25 days. The analysis of the t-test stated that there was an effect of giving common cold massage on the acceleration of the healing time of cold cough in baby and toddlers and statistically the difference was considered significant, because the p-value of 0.003 < 0.05. The combination of Common Cold Massage can speed up the healing time of cold cough symptoms.